2016
DOI: 10.1039/c5ra22840a
|View full text |Cite
|
Sign up to set email alerts
|

Sumac as a novel adjunctive treatment in hypertension: a randomized, double-blind, placebo-controlled clinical trial

Abstract: Sumac; a novel adjunctive treatment in Blood Pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…The biochemical biomarkers were adjusted for mean change of energy intake and physical activity (Table 5). (Ardakani, Vahidi, Karimi-Nazari, Dehghani, & Nadjarzadeh, 2016;Ardalani et al, 2016;Asgary et al, 2018;Heydari et al, 2019;Jaradat et al, 2017). In accordance with this study, the beneficial effects of sumac on weight and BMI were previously observed among hyperlipidemic obese (Asgary et al, 2018) and overweight or obese individuals (Heydari et al, 2019).…”
Section: Effects On Biochemical Assessmentssupporting
confidence: 86%
See 1 more Smart Citation
“…The biochemical biomarkers were adjusted for mean change of energy intake and physical activity (Table 5). (Ardakani, Vahidi, Karimi-Nazari, Dehghani, & Nadjarzadeh, 2016;Ardalani et al, 2016;Asgary et al, 2018;Heydari et al, 2019;Jaradat et al, 2017). In accordance with this study, the beneficial effects of sumac on weight and BMI were previously observed among hyperlipidemic obese (Asgary et al, 2018) and overweight or obese individuals (Heydari et al, 2019).…”
Section: Effects On Biochemical Assessmentssupporting
confidence: 86%
“…To our knowledge, this study is the first to evaluate the effects of sumac supplementation in combination with RCD on obesity and depression and to show some of its effects on a number of physiological pathways that are disturbed in obesity and mental health disorders. However, some in vitro study and clinical trials have investigated the effects of sumac on anthropometric indices in other metabolic disorders (Ardakani, Vahidi, Karimi‐Nazari, Dehghani, & Nadjarzadeh, 2016; Ardalani et al, 2016; Asgary et al, 2018; Heydari et al, 2019; Jaradat et al, 2017). In accordance with this study, the beneficial effects of sumac on weight and BMI were previously observed among hyperlipidemic obese (Asgary et al, 2018) and overweight or obese individuals (Heydari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antihypertensive activity of Rhus coriaria fruits could be attributed to flavonoids, which are the main chemical constituents of this plant, demonstrating the powerful cardiovascular protective activity of these compounds (Ardalani et al. 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, on two plants, chia (Nieman et al, 2009) and Rhus coriaria L. (Ardalani et al, 2016), it has been shown that they can increase the level of insulin secretion (Figure 2).…”
Section: Effect Of Herbal Medicines On Glycemic Indicesmentioning
confidence: 99%